The Mercantilist Index of Trade Policy. - Anderson, J; Neary, P (Boston College Department of Economics, 1998)
International trade policies are often compared across countries and over time for a variety of purposes. Analysts use such measures as arithmetic or trade-weighted average tariffs, Non-Tariff Barrier (NTB) coverage ratios and measures of tariff dispersion. All such measures are without theoretical foundation. In this paper we develop and characterise a theoretically-based index number of trade policy which is appropriate to trade negotiations. We characterize an index of trade policy restrictiveness defined as the uniform tariff equivalent which maintains the same volume of trade as a given set of tariffs, quotas, and domestic taxes and subsidies. We relate this volume-equivalent index to the Trade Restrictiveness Index, a welfare-equivalent measure, and relate changes in both indexes to changes in the generalised mean and variance of the tariff schedule. Applications to international cross-section and time-series comparisons of trade policy show that the new index frequently gives a very different picture than do standard indexes.